Electromyographic Evaluation of the Pelvic Muscles Activity After High-Intensity Focused Electromagnetic Procedure and Electrical Stimulation in Women With Pelvic Floor Dysfunction - Elena, Silantyeva; Dragana, Zarkovic; Ramina, Soldatskaia; Evgeniia, Astafeva; Orazov, Mekan (Sexual medicine, 2020)
INTRODUCTION: Impaired coordination, relaxation, and atrophy of pelvic floor muscles (PFMs) may cause various health issues referred to as pelvic floor dysfunction (PFD). In recent years, electromagnetic noninvasive stimulation of the pelvic floor was successfully used to treat PFD symptoms. AIM: This study aims to compare the effectiveness of electrical and magnetic noninvasive stimulation for the treatment of PFD in postpartum women. METHODS: 2 intervention groups treated with high-intensity focused electromagnetic ([HIFEM]; G1) procedure and electrical stimulation (G2) were established along with the control group (G3). Patients received 10 therapies delivered at the hospital (G1; 2-3 times per week) or self-administered at home (G2; every other day) after initial training. The protocol was identical for both modalities. Functionality of the PFM was examined by surface electromyography measurements (maximal voluntary contraction [MVC]; mean MVC; muscle activity at rest; endurance of contraction) while patient's subjective perception of pelvic floor functionality was assessed by Pelvic Floor Impact Questionnaire-Short Form 7 (PFIQ-7) standardized questionnaire. Changes in electromyography values and PFIQ-7 scores were statistically evaluated from baseline to after all treatments. MAIN OUTCOME MEASURE: The main outcome measure was enhancement of PFM activity. RESULTS: In total, 95 patients (G1 = 50; G2 = 25; G3 = 20) participated in the study. The MVC, mean MVC, and endurance were lowered in symptomatic patients. After the treatments, these parameters significantly increased (P < .001) and moved toward the values of healthy population. Electrogenesis at relaxation revealed divergent tendencies in the G1 and G2 groups. PFIQ-7 scores significantly improved in treated patients (P < .001). In general, superior results were documented in the HIFEM group as it reached improvement of electromyography parameters from 48% to 59% (electrical stimulation from 7% to 36%) and similarly the improvement of PFIQ-7 score by 57% (electrical stimulation by 32%). CONCLUSION: This study documented that the HIFEM procedure was significantly more effective than electrical stimulation in treatment of PFD in postpartum women. Both the objective and subjective evaluation indicates more profound effects of magnetic stimulation. Elena S, Dragana Z, Ramina S, et al. Electromyographic Evaluation of the Pelvic Muscles Activity After High-Intensity Focused Electromagnetic Procedure and Electrical Stimulation in Women With Pelvic Floor Dysfunction. Sex Med 2020;8:282-289.
Keywords: Electromyography; HIFEM Procedure; Electrical Stimulation; Pelvic Floor Muscles; Pelvic Floor Dysfunction